Antibacterial mildew-proof water-based adhesive and preparation method thereof
By preparing an antibacterial and mildew-proof water-based adhesive containing modified bio-based polyol and hybrid modified BN/MOF composite material, the problem of insufficient antibacterial and mildew-proof performance of existing bio-based high-crystalline water-based polyurethane adhesives is solved, and higher adhesion, water resistance and antibacterial and mildew-proof performance are achieved.
Patent Information
- Application Number
- CN202411700837.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The antibacterial and anti-mold properties of existing bio-based high-crystalline water-based polyurethane adhesives are insufficient, making it difficult to meet higher environmental protection and performance requirements.
An antibacterial and anti-mold-resistant aqueous adhesive including component A and component B is used. Component A is composed of modified bio-based polyols, hybrid modified BN/MOF composite materials, hexamethylene diisocyanate and 1,4-butanediol. Component B is an aliphatic curing agent. Through specific reaction steps and combinations, an adhesive with excellent adhesion, water resistance and anti-bacterial and anti-mold resistance is formed.
It improves the adhesion, water resistance and self-repair properties of the adhesive, and significantly improves its antibacterial and mildew resistance, which can effectively resist bacteria and fungi.
Smart Images

Figure CN119505791A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesives, in particular to an antibacterial and mildew-proof water-based adhesive and a preparation method thereof. Background Art
[0002] Water-based adhesives are environmentally friendly adhesives made from natural or synthetic polymers and water as solvent or dispersant, replacing toxic and harmful organic solvents. Water-based adhesives have become the current development trend of adhesives, among which water-based polyurethane adhesives are one of the most commonly used adhesives.
[0003] Biomass-based polyurethane is prepared from soybean oil, castor oil, palm oil, etc. as raw materials to produce vegetable oil-based polyols and isocyanates to replace petroleum-based polyols and isocyanates. It has the characteristics of renewable raw materials and low prices, and the product is safe and environmentally friendly. Therefore, the use of biomass-based polyurethane to prepare adhesives with excellent performance has attracted much attention. For example, Chinese patent CN114479742B provides a bio-based high-crystalline water-based polyurethane adhesive for shoes and a preparation process. The bio-based high-crystalline water-based polyurethane adhesive for shoes includes raw materials: bio-based polyester polyols, terminal hydroxyl polyether sulfonates, aliphatic diisocyanates, small molecule terminal hydroxyl chain extenders, small molecule terminal amino chain extenders, catalysts, defoamers, antibacterial agents, leveling agents and tackifying resins. The introduction of bio-based materials contributes to the sustainable development of mankind and environmental friendliness, but the antibacterial and mildew-proof properties of the adhesive need to be improved. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides an antibacterial and mildew-proof water-based adhesive, comprising component A and component B, and the antibacterial and mildew-proof water-based adhesive is prepared by the following method:
[0005] Step (1), 2-acetylbutyrolactone reacts with guanidine carbonate to obtain an intermediate product A; intermediate product A, bis(2-aminophenyl) disulfide, and 2,5-dihydroxyterephthalaldehyde react to obtain an intermediate product B;
[0006] Step (2), bis(2-mercaptoethyl) ether reacts with 4-pentenoyl chloride to obtain an intermediate product C; and the intermediate product C reacts with the intermediate product B to obtain a modifier;
[0007] Step (3), reacting 2,2-dihydroxymethylpropionic acid with castor oil to obtain a hyperbranched bio-based polyol; modifying the hyperbranched bio-based polyol with a modifier to obtain a modified bio-based polyol; using the modified bio-based polyol, the hybrid modified BN / MOF composite material, and hexamethylene diisocyanate as raw materials and 1,4-butanediol as a chain extender to prepare an aqueous polyurethane dispersion;
[0008] Wherein, the preparation method of the hybrid modified BN / MOF composite material comprises the following steps:
[0009] Step S1, treating a boron nitride micro-sheet with polydopamine to obtain a polydopamine-treated boron nitride micro-sheet; depositing copper-doped ZIF-8 on the surface of the polydopamine-treated boron nitride micro-sheet to obtain a BN / MOF composite material;
[0010] Step S2, loading citral into the BN / MOF composite material to obtain a loaded modified BN / MOF composite material; modifying the loaded modified BN / MOF composite material by chitosan to obtain a hybrid modified BN / MOF composite material;
[0011] Step (4), mixing an aqueous polyurethane dispersion, a wetting agent, a defoamer, a thickener, and water as component A; and using an aliphatic curing agent as component B;
[0012] When using, mix components A and B and stir.
[0013] Preferably, in step (1), the preparation method of the intermediate product B is:
[0014] 2-acetylbutyrolactone, guanidine carbonate and ethanol are uniformly mixed, and triethylamine is added, and the mixture is heated to 95-105°C and reacted for 4.5-5.5 hours. After the reaction is completed, the mixture is cooled to room temperature and purified to obtain an intermediate product A; wherein the mass ratio of 2-acetylbutyrolactone, guanidine carbonate, ethanol and triethylamine is (5.1-10.2):(4.8-9.6):(32-64):(8.1-16.2);
[0015] The intermediate product A is mixed with ethanol in a mass ratio of (1.7-3.4):(20-40), and stirred for 20-40 minutes to obtain a mixed solution; bis(2-aminophenyl) disulfide, 2,5-dihydroxyterephthalaldehyde, and ethanol are mixed in a mass ratio of (2.5-5):(1.7-3.4):(80-120), and then added to the mixed solution, heated to 55-65°C and reacted for 2.5-3.5 hours. After the reaction is completed, it is cooled to room temperature and purified to obtain an intermediate product B; wherein the mass ratio of the intermediate product A to bis(2-aminophenyl) disulfide is (1.7-3.4):(2.5-5);
[0016] In the above process, 2-acetylbutyrolactone and guanidine carbonate react to form an intermediate product A containing a ureidopyrimidone structure (i.e., a dimer of a UPy structure), and the dimer of the UPy structure can form a dynamic quadruple hydrogen bond; the aldehyde groups at both ends of 2,5-dihydroxyterephthalaldehyde react with the intermediate product A and the amino group of bis(2-aminophenyl)disulfide, respectively, to obtain an intermediate product B containing a ureidopyrimidone structure, a Schiff base bond, a disulfide bond, a hydroxyl group, an amino group and multiple benzene ring structures, wherein the Schiff base bond and the disulfide bond are dynamic bonds, the Schiff base bond can form a π-π conjugation with the benzene ring, and the Schiff base bond has a certain bactericidal effect.
[0017] Preferably, in step (2), the preparation method of the modifier is:
[0018] Mix bis(2-mercaptoethyl) ether, 4-pentenoyl chloride and N,N-dimethylformamide, and stir the mixture at room temperature for 4-5 hours. After the reaction is completed, purify the mixture to obtain an intermediate product C; wherein the mass ratio of bis(2-mercaptoethyl) ether, 4-pentenoyl chloride and N,N-dimethylformamide is (7.9-13.8):(10-15):(120-150);
[0019] In a nitrogen atmosphere, add the intermediate product C to tetrahydrofuran, stir for 20-40 minutes, then add the intermediate product B, stir and react at room temperature for 10-15 hours, then add a sodium bicarbonate aqueous solution with a concentration of 0.078 g / mL, continue stirring for 20-40 minutes, purify, and obtain a modifier; wherein the amount ratio of the intermediate product C, tetrahydrofuran, intermediate product B, and sodium bicarbonate aqueous solution is (2.6-5.2) g: (80-100) g: (5.5-11) g: (5.4-10.8) mL;
[0020] In the above process, the mercapto group of bis(2-mercaptoethyl) ether reacts with the carbon-carbon double bond of 4-pentenoyl chloride to obtain an intermediate product C; the acyl chloride in the intermediate product C reacts with the amino group of the intermediate product B to form an amide bond to obtain a modifier.
[0021] Preferably, in step (3), the preparation method of the modified bio-based polyol is:
[0022] Heat 2,2-dimethylolpropionic acid until it melts, then add castor oil and p-toluenesulfonic acid, maintain the reaction temperature at 180-190° C. in a nitrogen atmosphere, stir and react for 3-4 hours, collect the reaction product, purify it, and obtain a hyperbranched bio-based polyol; wherein the mass ratio of 2,2-dimethylolpropionic acid, castor oil, and p-toluenesulfonic acid is (8-16):(18.3-36.6):(0.03-0.06);
[0023] The hyperbranched bio-based polyol, the modifier and N,N-dimethylformamide are mixed, stirred and reacted at room temperature for 6-8 hours. After the reaction is completed, the mixture is purified to obtain a modified bio-based polyol; wherein the mass ratio of the hyperbranched bio-based polyol, the modifier and N,N-dimethylformamide is (10-20):(8-16):(150-200).
[0024] Preferably, in step (3), the preparation method of the aqueous polyurethane dispersion is:
[0025] The modified bio-based polyol, hybrid modified BN / MOF composite material, hexamethylene diisocyanate, and dibutyltin dilaurate were reacted at 75-85°C in a nitrogen atmosphere for 2.5-3.5 hours, then the temperature was raised to 85-95°C, 1,4-butanediol was added, and the reaction was continued for 3.5-4.5 hours. During the reaction, the viscosity of the reaction system was adjusted by adding acetone. After the reaction was completed, the reaction was cooled to 40-50°C, deionized water was added, and the mixture was heated to 1100- Stirring at a speed of 1300 r / min for 20-40 min, rotary evaporation, and obtaining an aqueous polyurethane dispersion; wherein the mass ratio of modified bio-based polyol, hybrid modified BN / MOF composite material, hexamethylene diisocyanate, dibutyltin dilaurate, 1,4-butanediol, and deionized water is (14.8-29.6):(1.5-2.5):(8-16):(0.03-0.05):(2-5):(50-70);
[0026] In the above process, 2,2-dihydroxymethylpropionic acid and castor oil are combined through an esterification reaction to obtain a hyperbranched bio-based polyol with more hydroxyl groups, and then the thiol group of the modifier reacts with the carbon-carbon double bond in the hyperbranched bio-based polyol to obtain a modified bio-based polyol; finally, the modified bio-based polyol, hybrid modified BN / MOF composite material, and hexamethylene diisocyanate are used as raw materials, and 1,4-butanediol is used as a chain extender to react, and the modified bio-based polyol is used to replace the petroleum-based polyol, and the hybrid modified BN / MOF composite material is connected to the polyurethane chain, and water is used as a dispersant to obtain an aqueous polyurethane dispersion.
[0027] Preferably, in step (3), the method for preparing the hybrid modified BN / MOF composite material comprises the following steps:
[0028] Step S1, adding the boron nitride micro-chip into Tris-HCl buffer, adjusting the pH value to 8.4-8.5 with a 0.1 mol / L NaOH aqueous solution, ultrasonically dispersing for 1-3 hours, then adding dopamine hydrochloride, stirring for reaction for 20-24 hours, centrifuging, washing, and drying to obtain a polydopamine-treated boron nitride micro-chip; wherein the amount ratio of the boron nitride micro-chip, Tris-HCl buffer, and dopamine hydrochloride is (5-8) g: (34-50) mL: (0.3-0.6) g;
[0029] Copper nitrate trihydrate was added into distilled water, stirred for 10-20 minutes, and then methanol was added to obtain a copper salt solution; the boron nitride micro-sheet treated with polydopamine was added into a zinc nitrate / methanol solution with a concentration of 0.026 g / mL, and soaked for 30-50 minutes, and then the copper salt solution and a 2-methylimidazole / methanol solution with a concentration of 0.021 g / mL were added, and ultrasonic treatment was performed in an ice water bath for 20-40 minutes, and then stirred at room temperature at a speed of 500-700 r / min. The mixture is stirred for 20-28 hours, centrifuged, washed, and dried to obtain a BN / MOF composite material; wherein the mass ratio of copper nitrate trihydrate, distilled water, and methanol in the copper salt solution is (6-12):(50-100):(160-320); the amount ratio of polydopamine-treated boron nitride microsheets, zinc nitrate / methanol solution, copper salt solution, and 2-methylimidazole / methanol solution is (5-8) g:(50-100) mL:(125-250) mL:(50-100) mL;
[0030] In the above process, dopamine hydrochloride is polymerized on the surface of boron nitride microsheets under alkaline conditions to form polydopamine, and abundant phenolic hydroxyl groups and imino groups are introduced on the surface of boron nitride microsheets to provide growth anchors for subsequent MOF, thereby realizing the in-situ growth of MOF. The growth of MOF material is based on zinc nitrate and copper nitrate as metal precursors, coordinated with 2-methylimidazole, to form a copper-doped ZIF-8 MOF material with a porous structure.
[0031] Step S2, mixing citral, BN / MOF composite material and ethanol, stirring for 30-40 hours, centrifuging, washing and drying to obtain a loaded modified BN / MOF composite material; wherein the mass ratio of citral, BN / MOF composite material and ethanol is (0.5-0.8):(3-5):(30-50);
[0032] The loaded modified BN / MOF composite material is dispersed in deionized water, ultrasonically dispersed for 10-20 minutes, a chitosan aqueous dispersion with a concentration of 10 mg / mL is added, stirred for 10-15 hours, centrifuged, washed, and dried to obtain a hybrid modified BN / MOF composite material; wherein the mass ratio of the loaded modified BN / MOF composite material, deionized water, and chitosan aqueous dispersion is (1-2):(100-150):(150-250);
[0033] In the above process, citral with antibacterial and antifungal effects is loaded into the BN / MOF composite material, and then the encapsulation of citral by chitosan is achieved through the metal chelation between the hydroxyl and amino groups in chitosan and MOF.
[0034] Preferably, in step (4), the contents of the components in component A are, by weight, 80-100 parts of aqueous polyurethane dispersion, 0.2-0.4 parts of wetting agent, 0.2-0.4 parts of defoaming agent, 0.2-0.5 parts of thickener, and 11-17 parts of water.
[0035] Preferably, in step (4), the wetting agent includes BYK-W961; the defoaming agent includes BYK-A515; the thickener includes BASF PU1190; and the aliphatic curing agent includes Covestro water-based curing agent BayhydurXP 2655.
[0036] Preferably, in step (4), the mass ratio of component A to component B is (18-24):1.
[0037] The antibacterial and mildew-proof water-based adhesive is prepared by the method for preparing the antibacterial and mildew-proof water-based adhesive.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] 1. The present invention uses bio-based material castor oil to prepare hyperbranched bio-based polyols for preparing aqueous polyurethane dispersions, thereby reducing the use of petroleum-based polyols and being more environmentally friendly; the polyols with hyperbranched structures can improve the crosslinking density of the polyurethane system, so that it has good comprehensive properties such as adhesion, water resistance, and thermal stability; the hyperbranched bio-based polyols are then modified and used as reaction raw materials to prepare polyurethane, and groups containing ureidopyrimidone structure, Schiff base bond, disulfide bond, hydroxyl group, amino group, and multiple benzene ring structures are introduced into the polyurethane system, and the adhesion and water resistance of the polyurethane system are improved through the coordination of quadruple hydrogen bonds, dynamic bonds, and π-π conjugation, and the antibacterial and mildew-proof properties of the polyurethane system are also improved due to the bactericidal properties of the Schiff base bonds. In addition, the introduction of quadruple hydrogen bonds and dynamic bonds also gives the polyurethane system good self-repairing properties.
[0040] 2. The present invention obtains a BN / MOF composite material by sequentially treating boron nitride microsheets with polydopamine and depositing copper-doped ZIF-8 MOF. The boron nitride microsheets can improve the mechanical strength of the polyurethane system, thereby improving the adhesion of the adhesive, and the sheet structure of the boron nitride microsheets can extend the water penetration path, thereby improving the water resistance of the adhesive; treating the boron nitride microsheets with polydopamine provides a growth anchor point for the in-situ growth of the MOF material, which is the key to achieving in-situ growth of the MOF material; and the MOF material prepared by the present invention is copper-doped ZIF-8 with a porous structure, and the copper-doped ZIF-8 releases zinc ions and copper ions with antibacterial properties, and the copper-doped ZIF-8 has better adhesion to bacteria and fungi. , thereby achieving better antibacterial and mildew proof effects; further, citral with antibacterial and mildew proof properties is loaded in the BN / MOF composite material and then encapsulated with chitosan. On the one hand, the controlled release of citral can be achieved and the release rate of citral can be slowed down. On the other hand, chitosan itself also has a good bactericidal and mildew proof effect, and chitosan is accessed on the surface of the loaded modified BN / MOF composite material to provide reactive groups for its participation in the polymerization of polyurethane, thereby increasing the cross-linking density of the polyurethane system and improving the dispersibility of the hybrid modified BN / MOF composite material in the adhesive system; therefore, the hybrid modified BN / MOF composite material of the present invention cooperates with the modified bio-based polyol to effectively improve the adhesion and water resistance of the adhesive and exert a lasting antibacterial and mildew proof property.
[0041] 3. The copper ions released from the hybrid modified BN / MOF composite material of the present invention can form coordination bonds with the Schiff base structure in the polyurethane polymer molecular chain, further promoting the cross-linking and cohesion between the polyurethane chains, and the copper ions can act as a catalyst to accelerate the exchange of disulfide bonds in the polyurethane system, thereby improving the adhesion, water resistance and self-healing efficiency of the adhesive. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is a process flow chart of the preparation method of the antibacterial and mildew-proof water-based adhesive of the present invention;
[0043] Figure 2 It is a schematic diagram of the synthesis of the intermediate product B of the present invention;
[0044] Figure 3 It is a schematic diagram of the synthesis of the intermediate product C of the present invention;
[0045] Figure 4 It is a test comparison chart of the antibacterial rate (0 day, 30 day) of Escherichia coli and Staphylococcus aureus of the antibacterial and mildew-proof water-based adhesives prepared in Examples 2-4 of the present invention and Comparative Examples 4-8;
[0046] Figure 5It is a test comparison chart of the lap shear strength (at room temperature, after immersion) of the antibacterial and mildew-proof water-based adhesives prepared in Examples 2-4 of the present invention and Comparative Examples 4-8. DETAILED DESCRIPTION
[0047] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0048] Example 1
[0049] This embodiment discloses a method for preparing a hybrid modified BN / MOF composite material, comprising the following steps:
[0050] Step S1, adding 6.5 g of boron nitride micro-sheets into 42 mL of Tris-HCl buffer, adjusting the pH value to 8.5 with a 0.1 mol / L NaOH aqueous solution, ultrasonically dispersing for 2 h, then adding 0.5 g of dopamine hydrochloride, stirring at room temperature at a speed of 300 r / min for 22 h, centrifuging, washing, and drying to obtain polydopamine-treated boron nitride micro-sheets;
[0051] 9 g of copper nitrate trihydrate was added to 75 g of distilled water, stirred for 15 min, and then 240 g of methanol was added to obtain a copper salt solution; 6.5 g of polydopamine-treated boron nitride micro-sheets were added to 75 mL of a 0.026 g / mL zinc nitrate / methanol solution, soaked for 40 min, and then 137.5 mL of the copper salt solution and 75 mL of a 0.021 g / mL 2-methylimidazole / methanol solution were added, and ultrasonic treatment was performed in an ice water bath for 30 min, and then stirred at room temperature at a speed of 600 r / min for 24 h, centrifuged, washed, and dried to obtain a BN / MOF composite material;
[0052] Step S2, 0.7 g of citral, 4 g of BN / MOF composite material, and 40 g of ethanol were mixed, stirred at room temperature at a speed of 300 r / min for 35 h, centrifuged, washed, and dried to obtain a loaded modified BN / MOF composite material;
[0053] 1.5 g of the loaded modified BN / MOF composite material was dispersed in 120 g of deionized water, ultrasonically dispersed for 15 min, 200 g of 10 mg / mL chitosan aqueous dispersion was added, stirred at 300 r / min for 12 h at room temperature, centrifuged, washed, and dried to obtain a hybrid modified BN / MOF composite material.
[0054] Example 2
[0055] This embodiment discloses a method for preparing an antibacterial and mildew-proof water-based adhesive, comprising the following steps:
[0056] Step (1), 5.1 g of 2-acetylbutyrolactone, 4.8 g of guanidine carbonate and 32 g of ethanol were mixed evenly, and then 8.1 g of triethylamine was added, heated to 95° C. and reacted for 5.5 h. After the reaction was completed, it was cooled to room temperature and filtered. The obtained filter residue was washed with ethanol three times and then vacuum dried to obtain an intermediate product A;
[0057] 1.7 g of intermediate product A was added to 20 g of ethanol and stirred for 20 min to obtain a mixed solution; 2.5 g of bis(2-aminophenyl) disulfide and 1.7 g of 2,5-dihydroxyterephthalaldehyde were dissolved in 80 g of ethanol, and then added to the mixed solution, heated to 55° C. and reacted for 3.5 h. After the reaction was completed, it was cooled to room temperature and filtered. The obtained filter residue was washed with ethanol 3 times and then vacuum dried to obtain intermediate product B;
[0058] Step (2), 7.9 g of bis(2-mercaptoethyl) ether, 10 g of 4-pentenoyl chloride, and 120 g of N,N-dimethylformamide were mixed, and the mixture was stirred at room temperature for 4 h. After the reaction was completed, the solvent and excess 4-pentenoyl chloride were removed by rotary evaporation at 70° C. to obtain an intermediate product C;
[0059] In a nitrogen atmosphere, 2.6 g of intermediate product C was added to 80 g of tetrahydrofuran, stirred for 20 min, and then 5.5 g of intermediate product B was added, stirred and reacted at room temperature for 10 h, and then 5.4 mL of 0.078 g / mL sodium bicarbonate aqueous solution was added, and stirring was continued for 20 min, filtered, washed, and dried to obtain a modifier;
[0060] Step (3), taking 8 g of 2,2-dihydroxymethylpropionic acid and heating it until it melts, then adding 18.3 g of castor oil and 0.03 g of p-toluenesulfonic acid, maintaining the reaction temperature at 180° C. in a nitrogen atmosphere, stirring the reaction for 3 h, collecting the reaction product, washing it with water, and drying it to obtain a hyperbranched bio-based polyol;
[0061] 10 g of hyperbranched bio-based polyol, 8 g of modifier, and 150 g of N,N-dimethylformamide were mixed, and stirred at room temperature for 6 h. After the reaction, the solvent was removed by rotary evaporation at 70 ° C to obtain a modified bio-based polyol;
[0062] 14.8 g of modified bio-based polyol, 1.5 g of hybrid modified BN / MOF composite material, 8 g of hexamethylene diisocyanate, and 0.03 g of dibutyltin dilaurate were reacted at 75 °C for 3.5 h in a nitrogen atmosphere, then heated to 85 °C, 2 g of 1,4-butanediol was added as a chain extender, and the reaction was continued for 4.5 h. During the reaction, the viscosity of the reaction system was adjusted by adding acetone. After the reaction was completed, the mixture was cooled to 40 °C, 50 g of deionized water was added, and the mixture was stirred at a speed of 1100 r / min for 40 min. The acetone was removed by rotary evaporation to obtain an aqueous polyurethane dispersion.
[0063] Step (4), by weight, 80 parts of aqueous polyurethane dispersion, 10.2 parts of BYK-W96, 10.2 parts of BYK-A515, 0.2 parts of BASF PU1190, and 11 parts of water are mixed to obtain component A;
[0064] Take Covestro water-based curing agent BayhydurXP 2655 as component B;
[0065] When using, mix component A and component B in a mass ratio of 18:1 and stir at a speed of 150 r / min for 5 minutes.
[0066] Example 3
[0067] This embodiment discloses a method for preparing an antibacterial and mildew-proof water-based adhesive, comprising the following steps:
[0068] Step (1), 10.2 g of 2-acetylbutyrolactone, 9.6 g of guanidine carbonate and 64 g of ethanol were mixed evenly, and then 16.2 g of triethylamine was added, heated to 105° C. and reacted for 4.5 h. After the reaction was completed, it was cooled to room temperature and filtered. The obtained filter residue was washed with ethanol 5 times and then vacuum dried to obtain an intermediate product A;
[0069] 3.4 g of intermediate product A was added to 40 g of ethanol and stirred for 40 min to obtain a mixed solution; 5 g of bis(2-aminophenyl) disulfide and 3.4 g of 2,5-dihydroxyterephthalaldehyde were dissolved in 120 g of ethanol, and then added to the mixed solution, heated to 65° C. and reacted for 2.5 h. After the reaction was completed, the mixture was cooled to room temperature and filtered. The obtained filter residue was washed with ethanol 5 times and then vacuum dried to obtain intermediate product B;
[0070] Step (2), 13.8 g of bis(2-mercaptoethyl) ether, 15 g of 4-pentenoyl chloride, and 150 g of N,N-dimethylformamide were mixed, and the mixture was stirred at room temperature for 5 h. After the reaction was completed, the solvent and excess 4-pentenoyl chloride were removed by rotary evaporation at 80° C. to obtain an intermediate product C;
[0071] In a nitrogen atmosphere, 5.2 g of intermediate product C was added to 100 g of tetrahydrofuran, stirred for 40 min, and then 11 g of intermediate product B was added, stirred and reacted at room temperature for 15 h, and then 10.8 mL of a 0.078 g / mL sodium bicarbonate aqueous solution was added, and stirring was continued for 40 min, filtered, washed, and dried to obtain a modifier;
[0072] Step (3), taking 16 g of 2,2-dihydroxymethylpropionic acid and heating it until it melts, then adding 36.6 g of castor oil and 0.06 g of p-toluenesulfonic acid, maintaining the reaction temperature at 190° C. in a nitrogen atmosphere, stirring the reaction for 3 h, collecting the reaction product, washing it with water, and drying it to obtain a hyperbranched bio-based polyol;
[0073] 20 g of hyperbranched bio-based polyol, 16 g of modifier, and 200 g of N,N-dimethylformamide were mixed, and stirred for reaction at room temperature for 8 h. After the reaction was completed, the solvent was removed by rotary evaporation at 80 ° C to obtain a modified bio-based polyol;
[0074] 29.6 g of modified bio-based polyol, 2.5 g of hybrid modified BN / MOF composite material, 16 g of hexamethylene diisocyanate, and 0.05 g of dibutyltin dilaurate were reacted at 85° C. for 2.5 h in a nitrogen atmosphere, then heated to 95° C., 5 g of 1,4-butanediol was added as a chain extender, and the reaction was continued for 3.5 h. During the reaction, the viscosity of the reaction system was adjusted by adding acetone. After the reaction was completed, the mixture was cooled to 50° C., 70 g of deionized water was added, and the mixture was stirred at a speed of 1300 r / min for 20 min. The acetone was removed by rotary evaporation to obtain an aqueous polyurethane dispersion.
[0075] Step (4), by weight, 100 parts of aqueous polyurethane dispersion, 10.4 parts of BYK-W96, 10.4 parts of BYK-A515, 0.5 parts of BASF PU1190, and 17 parts of water are mixed to obtain component A;
[0076] Take Covestro water-based curing agent BayhydurXP 2655 as component B;
[0077] When using, component A and component B are mixed in a mass ratio of 24:1 and stirred at a speed of 250 r / min for 3 minutes.
[0078] Example 4
[0079] This embodiment discloses a method for preparing an antibacterial and mildew-proof water-based adhesive, comprising the following steps:
[0080] Step (1), 7.7 g of 2-acetylbutyrolactone, 7.2 g of guanidine carbonate and 48 g of ethanol were mixed evenly, and then 12.2 g of triethylamine was added, heated to 100° C. and reacted for 5 h. After the reaction was completed, it was cooled to room temperature and filtered. The filter residue was washed with ethanol 4 times and then vacuum dried to obtain an intermediate product A;
[0081] 2.6 g of intermediate product A was added to 30 g of ethanol and stirred for 30 min to obtain a mixed solution; 3.8 g of bis(2-aminophenyl) disulfide and 2.6 g of 2,5-dihydroxyterephthalaldehyde were dissolved in 100 g of ethanol, and then added to the mixed solution, heated to 60° C. and reacted for 3 h. After the reaction was completed, the mixture was cooled to room temperature and filtered. The obtained filter residue was washed with ethanol 4 times and then vacuum dried to obtain intermediate product B;
[0082] Step (2), 10.9 g of bis(2-mercaptoethyl) ether, 12.5 g of 4-pentenoyl chloride, and 135 g of N,N-dimethylformamide were mixed, and the mixture was stirred at room temperature for 4.5 h. After the reaction was completed, the solvent and excess 4-pentenoyl chloride were removed by rotary evaporation at 75° C. to obtain an intermediate product C;
[0083] In a nitrogen atmosphere, 3.9 g of intermediate product C was added to 90 g of tetrahydrofuran, stirred for 30 min, and then 8.3 g of intermediate product B was added, stirred and reacted at room temperature for 12 h, and then 8.1 mL of 0.078 g / mL sodium bicarbonate aqueous solution was added, and stirring was continued for 30 min, filtered, washed, and dried to obtain a modifier;
[0084] Step (3), taking 12 g of 2,2-dihydroxymethylpropionic acid and heating it until it melts, then adding 27.5 g of castor oil and 0.05 g of p-toluenesulfonic acid, maintaining the reaction temperature at 185° C. in a nitrogen atmosphere, stirring the reaction for 3.5 h, collecting the reaction product, washing it with water, and drying it to obtain a hyperbranched bio-based polyol;
[0085] 15 g of hyperbranched bio-based polyol, 12 g of modifier, and 175 g of N,N-dimethylformamide were mixed, and stirred for reaction at room temperature for 7 h. After the reaction was completed, the solvent was removed by rotary evaporation at 75 ° C to obtain a modified bio-based polyol;
[0086] 22.2g of modified bio-based polyol, 2g of hybrid modified BN / MOF composite material, 12g of hexamethylene diisocyanate, and 0.04g of dibutyltin dilaurate were reacted at 80°C for 3h in a nitrogen atmosphere, then heated to 90°C, 3.5g of 1,4-butanediol was added as a chain extender, and the reaction was continued for 4h. During the reaction, the viscosity of the reaction system was adjusted by adding acetone. After the reaction was completed, the mixture was cooled to 45°C, 60g of deionized water was added, and the mixture was stirred at a speed of 1200r / min for 30min. The acetone was removed by rotary evaporation to obtain an aqueous polyurethane dispersion.
[0087] Step (4), by weight, 90 parts of aqueous polyurethane dispersion, 10.3 parts of BYK-W96, 10.3 parts of BYK-A515, 0.4 parts of BASF PU1190, and 14 parts of water are mixed to obtain component A;
[0088] Take Covestro water-based curing agent BayhydurXP 2655 as component B;
[0089] When used, component A and component B are mixed in a mass ratio of 21:1 and stirred at a speed of 200 r / min for 4 minutes.
[0090] The hybrid modified BN / MOF composite material used in the above Examples 2-4 is the hybrid modified BN / MOF composite material prepared in Example 1.
[0091] Comparative Example 1
[0092] Compared with Example 1, in the process of preparing the BN / MOF composite material in Comparative Example 1, no polydopamine-treated boron nitride microsheets were added, that is, the BN / MOF composite material was replaced by MOF material in this comparative example, and the final product of Comparative Example 1 was a hybrid modified MOF composite material, while other conditions remained unchanged.
[0093] Comparative Example 2
[0094] Compared with Example 1, in the process of preparing the BN / MOF composite material in Comparative Example 2, no copper salt solution was added, and other conditions remained unchanged.
[0095] Comparative Example 3
[0096] Compared with Example 1, in the process of preparing the hybrid modified BN / MOF composite material in Comparative Example 3, the BN / MOF composite material is used instead of the loaded modified BN / MOF composite material, that is, citral is not loaded in the hybrid modified BN / MOF composite material of Comparative Example 3, and other conditions remain unchanged.
[0097] Comparative Example 4
[0098] Compared with Example 4, in the process of preparing the aqueous polyurethane dispersion in Comparative Example 4, the loaded modified BN / MOF composite material was used instead of the hybrid modified BN / MOF composite material, and other conditions remained unchanged.
[0099] Comparative Example 5
[0100] Compared with Example 4, in the process of preparing the aqueous polyurethane dispersion in Comparative Example 5, the hybrid modified MOF composite material prepared in Comparative Example 1 was used, and other conditions remained unchanged.
[0101] Comparative Example 6
[0102] Compared with Example 4, in the process of preparing the aqueous polyurethane dispersion in Comparative Example 6, the hybrid modified BN / MOF composite material prepared in Comparative Example 2 was used, and other conditions remained unchanged.
[0103] Comparative Example 7
[0104] Compared with Example 4, in the process of preparing the aqueous polyurethane dispersion in Comparative Example 7, the hybrid modified BN / MOF composite material prepared in Comparative Example 3 was used, and other conditions remained unchanged.
[0105] Comparative Example 8
[0106] Compared with Example 4, in Comparative Example 8, during the preparation of the aqueous polyurethane dispersion, hyperbranched bio-based polyol was used instead of modified bio-based polyol, and other conditions remained unchanged.
[0107] In the above examples and comparative examples, Tris-HCl buffer, with a concentration of 0.01 mol / L and a pH of 8.0, was obtained from Shanghai Yuanye Biotechnology Co., Ltd.; boron nitride microsheets, with an average diameter of 5±1 μm and a specific surface area of 4.5 m 2 / g, item number DCB-05F, from Dongguan Dongchao New Materials Technology Co., Ltd.; chitosan, molecular weight 190000-310000Da, viscosity 200-800cPs, deacetylation degree 75%-85%, from Sigma-Aldrich; castor oil, CAS: 8001-79-4, purity: 99.9%, from Shandong Fengpan New Materials Co., Ltd.; BYK-W961, from Shanghai Longdi Chemical Co., Ltd.; BYK-A515, from Shenzhen Longdi Chemical Co., Ltd.; BASF PU1190, from Guangzhou Si Tuyuan Chemical Co., Ltd.; Covestro water-based curing agent BayhydurXP 2655, viscosity (23℃): 3500±1000mPa·s, type: hydrophilic aliphatic polyisocyanate based on hexamethylene diisocyanate (HDI), from Shanghai David New Materials Co., Ltd.
[0108] Experimental example
[0109] The performance of the antibacterial and mildew-proof water-based adhesives prepared in Examples 2-4 and Comparative Examples 4-8 was tested.
[0110] 1. Adhesion performance test: According to GB / T 7124-2008, a lap shear test was carried out to detect the adhesion performance of each group of samples after being immersed in water at room temperature and 25°C for 5 days.
[0111] 2. Antibacterial performance test: Tested in accordance with JIS Z2801-2012, the test bacteria are Escherichia coli ATCC 25922 and Staphylococcus aureus ATCC 6538P.
[0112] 3. Anti-mildew performance test: Tested in accordance with JIS Z2911-2018, the test fungi used are Aspergillus niger ATCC 6275, Penicillium pinophilum ATCC 36839, Paecilomyces variotii ATCC 18502, Trichoderma viride ATCC 9645 and Chaetomium globosum ATCC6205.
[0113] 4. Self-repairing performance test: Test the elongation at break according to the method specified in GB / T 528-2009. Cut the dumbbell spline from the middle of the gauge section, splice it, and treat it in a 40℃ oven for 6 hours to test the elongation at break. The self-repairing efficiency is evaluated by the retention rate of the elongation at break.
[0114] The test results are shown in Table 1:
[0115] Table 1
[0116]
[0117]
[0118] It can be seen from the test results in Table 1 that the antibacterial and mildew-proof water-based adhesives prepared in Examples 2-4 of the present invention have excellent adhesion performance, water resistance, self-repairing performance and durable antibacterial and mildew-proof performance.
[0119] From the comparison between Comparative Example 4 and Implementation 4, it can be seen that by loading citral with antibacterial and mildew-proof properties in the BN / MOF composite material and then encapsulating it with chitosan, on the one hand, the controlled release of citral can be achieved and the release rate of citral can be slowed down. On the other hand, chitosan itself also has a good bactericidal and mildew-proof effect, and chitosan is connected to the surface of the loaded modified BN / MOF composite material to provide a reactive group for its participation in the polymerization of polyurethane, thereby increasing the crosslinking density of the polyurethane system and improving the dispersibility of the hybrid modified BN / MOF composite material in the adhesive system, thereby improving the adhesion performance, water resistance, and lasting antibacterial and mildew-proof properties of the adhesive; from the comparison between Comparative Example 5 and Implementation 4, it can be seen that the boron nitride microsheets can improve the mechanical strength of the polyurethane system, thereby improving the adhesion of the adhesive, and because the sheet structure of the boron nitride microsheets can extend the water penetration path, thereby improving the adhesive Water resistance of the adhesive; from the comparison of comparative example 6 and implementation 4, it can be seen that copper-doped ZIF-8 can release zinc ions and copper ions with antibacterial properties, and copper-doped ZIF-8 has better adhesion to bacteria and fungi, thereby achieving better antibacterial and mildew proof effects, and due to the effect of copper ions on the Schiff base structure and the promotion of disulfide bond exchange, the adhesion, water resistance and self-repair efficiency of the adhesive are improved; from the comparison of comparative example 7 and implementation 4, it can be seen that the sustained release of citral has a positive effect on improving the antibacterial and mildew proof properties of the adhesive; from the comparison of comparative example 8 and implementation 4, it can be seen that the hyperbranched bio-based polyol is modified and then used as a reaction raw material to prepare a polyurethane, and groups containing ureidopyrimidone structure, Schiff base bond, disulfide bond, hydroxyl group, amino group and multiple benzene ring structures are introduced into the polyurethane system, thereby improving the comprehensive performance of the adhesive.
[0120] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. An antibacterial and mildew-proof water-based adhesive, comprising component A and component B, characterized in that: Prepared by the following method: Step (1), 2-acetylbutyrolactone reacts with guanidine carbonate to obtain an intermediate product A; intermediate product A, bis(2-aminophenyl) disulfide, and 2,5-dihydroxyterephthalaldehyde react to obtain an intermediate product B; Step (2), bis(2-mercaptoethyl) ether reacts with 4-pentenoyl chloride to obtain an intermediate product C; and the intermediate product C reacts with the intermediate product B to obtain a modifier; Step (3), reacting 2,2-dihydroxymethylpropionic acid with castor oil to obtain a hyperbranched bio-based polyol; modifying the hyperbranched bio-based polyol with a modifier to obtain a modified bio-based polyol; using the modified bio-based polyol, the hybrid modified BN / MOF composite material, and hexamethylene diisocyanate as raw materials and 1,4-butanediol as a chain extender to prepare an aqueous polyurethane dispersion; Wherein, the preparation method of the hybrid modified BN / MOF composite material comprises the following steps: Step S1, treating a boron nitride micro-sheet with polydopamine to obtain a polydopamine-treated boron nitride micro-sheet; depositing copper-doped ZIF-8 on the surface of the polydopamine-treated boron nitride micro-sheet to obtain a BN / MOF composite material; Step S2, loading citral into the BN / MOF composite material to obtain a loaded modified BN / MOF composite material; modifying the loaded modified BN / MOF composite material by chitosan to obtain a hybrid modified BN / MOF composite material; Step (4), mixing the aqueous polyurethane dispersion, the wetting agent, the defoaming agent, the thickener and water as component A; and using the aliphatic curing agent as component B.
2. The method for preparing the antibacterial and mildew-proof water-based adhesive according to claim 1, characterized in that: In the step (1), the preparation method of the intermediate product B is: 2-acetylbutyrolactone, guanidine carbonate and ethanol are uniformly mixed, and triethylamine is added, and the mixture is heated to 95-105°C and reacted for 4.5-5.5 hours. After the reaction is completed, the mixture is cooled to room temperature and purified to obtain an intermediate product A; wherein the mass ratio of 2-acetylbutyrolactone, guanidine carbonate, ethanol and triethylamine is (5.1-10.2):(4.8-9.6):(32-64):(8.1-16.2); The intermediate product A is mixed with ethanol in a mass ratio of (1.7-3.4):(20-40), and stirred for 20-40 minutes to obtain a mixed solution; bis(2-aminophenyl) disulfide, 2,5-dihydroxyterephthalaldehyde, and ethanol are mixed in a mass ratio of (2.5-5):(1.7-3.4):(80-120), and then added to the above mixed solution, heated to 55-65°C and reacted for 2.5-3.5 hours. After the reaction is completed, it is cooled to room temperature and purified to obtain an intermediate product B; wherein the mass ratio of the intermediate product A and bis(2-aminophenyl) disulfide is (1.7-3.4):(2.5-5).
3. The method for preparing the antibacterial and mildew-proof water-based adhesive according to claim 1, characterized in that: In the step (2), the preparation method of the modifier is: Mix bis(2-mercaptoethyl) ether, 4-pentenoyl chloride and N,N-dimethylformamide, and stir the mixture at room temperature for 4-5 hours. After the reaction is completed, purify the mixture to obtain an intermediate product C; wherein the mass ratio of bis(2-mercaptoethyl) ether, 4-pentenoyl chloride and N,N-dimethylformamide is (7.9-13.8):(10-15):(120-150); In a nitrogen atmosphere, the intermediate product C is added to tetrahydrofuran, stirred for 20-40 minutes, and then the intermediate product B is added, and the reaction is stirred at room temperature for 10-15 hours, and then a sodium bicarbonate aqueous solution with a concentration of 0.078 g / mL is added, and the stirring is continued for 20-40 minutes, and the modifier is obtained after purification; wherein the amount ratio of the intermediate product C, tetrahydrofuran, intermediate product B, and sodium bicarbonate aqueous solution is (2.6-5.2) g: (80-100) g: (5.5-11) g: (5.4-10.8) mL.
4. The method for preparing the antibacterial and mildew-proof water-based adhesive according to claim 1, characterized in that: In the step (3), the preparation method of the modified bio-based polyol is: Heat 2,2-dimethylolpropionic acid until it melts, then add castor oil and p-toluenesulfonic acid, maintain the reaction temperature at 180-190° C. in a nitrogen atmosphere, stir and react for 3-4 hours, collect the reaction product, purify it, and obtain a hyperbranched bio-based polyol; wherein the mass ratio of 2,2-dimethylolpropionic acid, castor oil, and p-toluenesulfonic acid is (8-16):(18.3-36.6):(0.03-0.06); The hyperbranched bio-based polyol, the modifier and N,N-dimethylformamide are mixed, stirred and reacted at room temperature for 6-8 hours. After the reaction is completed, the mixture is purified to obtain a modified bio-based polyol; wherein the mass ratio of the hyperbranched bio-based polyol, the modifier and N,N-dimethylformamide is (10-20):(8-16):(150-200).
5. The method for preparing the antibacterial and mildew-proof water-based adhesive according to claim 1, characterized in that: In the step (3), the preparation method of the aqueous polyurethane dispersion is: The modified bio-based polyol, hybrid modified BN / MOF composite material, hexamethylene diisocyanate, and dibutyltin dilaurate were reacted at 75-85°C in a nitrogen atmosphere for 2.5-3.5 hours, then the temperature was raised to 85-95°C, 1,4-butanediol was added, and the reaction was continued for 3.5-4.5 hours. During the reaction, the viscosity of the reaction system was adjusted by adding acetone. After the reaction was completed, the reaction was cooled to 40-50°C, deionized water was added, and the mixture was heated to 1100- The mixture was stirred at a speed of 1300 r / min for 20-40 min and rotary evaporated to obtain an aqueous polyurethane dispersion; wherein the mass ratio of modified bio-based polyol, hybrid modified BN / MOF composite material, hexamethylene diisocyanate, dibutyltin dilaurate, 1,4-butanediol and deionized water was (14.8-29.6):(1.5-2.5):(8-16):(0.03-0.05):(2-5):(50-70).
6. The method for preparing the antibacterial and mildew-proof water-based adhesive according to claim 1, characterized in that: In the step (3), the method for preparing the hybrid modified BN / MOF composite material comprises the following steps: Step S1, adding the boron nitride micro-chip into Tris-HCl buffer, adjusting the pH value to 8.4-8.5 with a 0.1 mol / L NaOH aqueous solution, ultrasonically dispersing for 1-3 hours, then adding dopamine hydrochloride, stirring for reaction for 20-24 hours, centrifuging, washing, and drying to obtain a polydopamine-treated boron nitride micro-chip; wherein the amount ratio of the boron nitride micro-chip, Tris-HCl buffer, and dopamine hydrochloride is (5-8) g: (34-50) mL: (0.3-0.6) g; Copper nitrate trihydrate was added into distilled water, stirred for 10-20 minutes, and then methanol was added to obtain a copper salt solution; the boron nitride micro-sheet treated with polydopamine was added into a zinc nitrate / methanol solution with a concentration of 0.026 g / mL, and soaked for 30-50 minutes, and then the copper salt solution and a 2-methylimidazole / methanol solution with a concentration of 0.021 g / mL were added, and ultrasonic treatment was performed in an ice water bath for 20-40 minutes, and then stirred at room temperature at a speed of 500-700 r / min. The mixture is stirred for 20-28 hours, centrifuged, washed, and dried to obtain a BN / MOF composite material; wherein the mass ratio of copper nitrate trihydrate, distilled water, and methanol in the copper salt solution is (6-12):(50-100):(160-320); the amount ratio of polydopamine-treated boron nitride microsheets, zinc nitrate / methanol solution, copper salt solution, and 2-methylimidazole / methanol solution is (5-8) g:(50-100) mL:(125-250) mL:(50-100) mL; Step S2, mixing citral, BN / MOF composite material and ethanol, stirring for 30-40 hours, centrifuging, washing and drying to obtain a loaded modified BN / MOF composite material; wherein the mass ratio of citral, BN / MOF composite material and ethanol is (0.5-0.8):(3-5):(30-50); The loaded modified BN / MOF composite material is dispersed in deionized water, ultrasonically dispersed for 10-20 minutes, a chitosan aqueous dispersion with a concentration of 10 mg / mL is added, stirred for 10-15 hours, centrifuged, washed, and dried to obtain a hybrid modified BN / MOF composite material; wherein the mass ratio of the loaded modified BN / MOF composite material, deionized water, and chitosan aqueous dispersion is (1-2):(100-150):(150-250).
7. The method for preparing the antibacterial and mildew-proof water-based adhesive according to claim 1, characterized in that: In the step (4), the contents of the components in component A are, by weight, 80-100 parts of aqueous polyurethane dispersion, 0.2-0.4 parts of wetting agent, 0.2-0.4 parts of defoaming agent, 0.2-0.5 parts of thickener, and 11-17 parts of water.
8. The method for preparing the antibacterial and mildew-proof water-based adhesive according to claim 1, characterized in that: In the step (4), the wetting agent includes BYK-W961; the defoaming agent includes BYK-A515; the thickener includes BASF PU1190; and the aliphatic curing agent includes Covestro water-based curing agent BayhydurXP 2655.
9. The method for preparing the antibacterial and mildew-proof water-based adhesive according to claim 1, characterized in that: In the step (4), the mass ratio of component A to component B is (18-24):
1.
10. An antibacterial and mildew-proof water-based adhesive prepared by the method for preparing an antibacterial and mildew-proof water-based adhesive as claimed in any one of claims 1 to 9.
Citation Information
Patent Citations
A bio-based, highly crystalline waterborne polyurethane adhesive for footwear and its preparation process.
CN114479742B
Safe and environment-friendly waterborne antibacterial adhesive with high performance and preparation method thereof
CN108395867A
High-temperature-resistant two-component polyurethane structural adhesive for power battery and preparation method thereof
CN116574478A
Preparation method of antibacterial master batch
CN116622099A
Macroporous non-fine concrete and preparation method thereof
CN118084444A
Cited By
Polyurethane hot melt adhesive composition and application thereof
CN119799250A
Water-based Teflon coating and preparation method thereof
CN120944418A
Aqueous teflon coating and method of making same
CN120944418B
Environment-friendly adhesive as well as preparation method and application thereof
CN122357071A